MORPHOMETRIC AND VULNERABILITY ANALYSIS OF GADA RIVER BASIN TO EROSION AND SEDIMENT YIELD (FUDMA JOURNAL OF SCIENCES, 2023)
This study is on morphometric analysis of River Gada using Geographical Information System (GIS) techniques. The aim of the study is to establish a relationship between surface morphometry and the hydrogeomorphic characteristics of the basin. This is crucial for analyzing the vulnerability of Gada river basin to erosion and sediment yield. For detailed measurement and analysis, Digital Elevation Model (DEM), high resolution imageries, and thematic maps were employed for basin delineation, slope characterization, channel network extraction and stream ordering in order to derive the linear, areal, and relief aspects of morphometric parameters of the study basin. The findings of the study revealed that a total number of 67 streams joined the 4th order stream in which 52 streams were 1st order, 11 streams were 2nd order, 4 streams were 3rd order and the major trunk was 4th order stream, occupied an area of 2,790.72km2. The drainage pattern of the stream network was dendritic pattern. The results further indicate that the values for stream frequency, bifurcation ratio, drainage density, drainage texture, constant channel maintenance, circularity ratio, elongation ratio, length of overland flow, relief ratio, dissection index, ruggedness number, and gradient ratio are 0.02, 3.83, 0.23km/km2, 0.005km per km2, 0.35sqft, 0.51, 0.83, 0.71km, 1.15, 0.38, 0.063 and 0.43 respectively. The observed values of both linear, areal and relief parameters were generally low. For linear parameters, low values indicate higher unit area sediment yield and low erosion vulnerability, while for areal and relief parameters, low values  represent a symptom of youthful stage of
Keywords: Morphometric Analysis, Gada River Basin, Digital Elevation Model (DEM), Geographical Information System (GIS)